Desalination : discharging brine into coastal waters (square 30 degree angle) - Lim, Zhong Yi. (2009)
The vortices in a square nozzle encourage more entrainment than round nozzle in principle, and thus should increase mixing. This is due to the characteristic of the vortices created by the nozzle geometry.